2018
DOI: 10.1111/raq.12316
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics and fish nutrition: a review in the context of sustainable feed development

Abstract: Aquaculture is facing a strategic challenge to improve feed suitability and support the global increase in fish production. Improvements in diet formulation for sustainable nutritional strategies have focused to date on the partial substitution of marine resources by plant resources but will now include other alternative feedstuffs. Growth trials and body composition data provide valuable indicators of fish nutritional status, while omics technologies may contribute to a better understanding of fish nutrition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
87
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(89 citation statements)
references
References 137 publications
(351 reference statements)
1
87
0
1
Order By: Relevance
“…Consistent with the present study, work in teleosts demonstrated that poly (I:C) induced ifnγ to stimulate respiratory burst activity in vitro (Grayfer & Belosevic, 2009) and in vivo (Zhou et al, 2014;Zhu et al, 2019). are essential AAs for fish (Halver et al, 1957;National Research Council, 2011;Wilson, 2002) and are involved in energy metabolism (Roques et al, 2018b;Wagner et al, 2014).…”
Section: Fish Immune Gene Expressionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with the present study, work in teleosts demonstrated that poly (I:C) induced ifnγ to stimulate respiratory burst activity in vitro (Grayfer & Belosevic, 2009) and in vivo (Zhou et al, 2014;Zhu et al, 2019). are essential AAs for fish (Halver et al, 1957;National Research Council, 2011;Wilson, 2002) and are involved in energy metabolism (Roques et al, 2018b;Wagner et al, 2014).…”
Section: Fish Immune Gene Expressionsupporting
confidence: 88%
“…Metabolites associated with the valine, leucine and isoleucine biosynthesis pathway were upregulated in fish serum (Figure ). The three branched‐chain amino acids (BCAA) are essential AAs for fish (Halver et al ., ; National Research Council, ; Wilson, ) and are involved in energy metabolism (Roques et al ., ; Wagner et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…Tissue metabolite profiling using nuclear magnetic resonance (NMR) is being increasingly applied in the aquaculture field, for example, to evaluate the effects of different rearing conditions [11,12] or to determine the influence of alternative dietary ingredients on the tissue metabolome [13,14]. These and other applications were recently reviewed by Roques et al [15].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics has recently begun to be used in fish nutrition to analyse the effects of feeding ( 26 , 27 ) , the impact of a wild v. a natural diet ( 23 ) and the effects of feed ingredients ( 28 32 ) , and more recently, to evaluate the development of new diets ( 33 36 ) . The two main metabolomic approaches are proton nuclear magnetic resonance ( 1 H-NMR) and mass spectrometry, each having their own advantages and technical limitations ( 37 ) . NMR is not sensitive and selective with only a few dozens of metabolites detected and identified requiring a significant sample size.…”
mentioning
confidence: 99%